Strategi Pembelajaran Analogi dan Kemampuan Pemahaman Konsep Matematika - Ketut Rendrayana; I Made Suarsana; Ni Nyoman Parwati (Jurnal Pendidikan Matematika RAFA, 2020)
This study aimed to determine the effect of analogy learning strategies on the ability to mathematical conceptual understanding. This research is a quasi-experimental study using pretest-posttest control group design. The research population was class VIII of SMP Negeri 2 Sawan in the academic year 2019/2020, which was then sampled using cluster random sampling techniques to obtain students in class VIIIA and VIIIC as an experimental group and students in class VIIIB and VIIID as a control group. The ability to understand students' mathematical concepts was tested using essays tests both pre-test and post-test. After the data is collected, it is then analyzed using the one-way ANACOVA test with a significance level of 5%. Based on the results of research conducted, obtained FA * = 17,369 ≥ F table = 3,918. These results indicate that the student sability to understand mathematical concepts who are taught by using analogy learning strategies are better than conventional learning. Therefore analogy learning strategies have a positive influence on the ability to understand mathematical concepts.